On the Origin of Chirality in Nanoplasmonic Gyroid Metamaterials. (26th October 2012) - Oh, Sang Soon; Demetriadou, Angela; Wuestner, Sebastian; Hess, Ortwin
<x xml:space="preserve">Abstract</x> Metallic single gyroids, a new class of self‐assembled nanoplasmonic metamaterials, are analyzed on the basis of a tri‐helical metamaterial model. The physical mechanisms underlying the chiral optical behavior of the nanoplasmonic single gyroid are identified and it is shown that the optical chirality in this metallic structure is primarily determined by structural chirality and the connectivity of helices along the main cubic axes. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>